2x-(3+x)=

Simple and best practice solution for 2x-(3+x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-(3+x)= equation:


Simplifying
2x + -1(3 + x) = 0
2x + (3 * -1 + x * -1) = 0
2x + (-3 + -1x) = 0

Reorder the terms:
-3 + 2x + -1x = 0

Combine like terms: 2x + -1x = 1x
-3 + 1x = 0

Solving
-3 + 1x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 1x = 0 + 3

Combine like terms: -3 + 3 = 0
0 + 1x = 0 + 3
1x = 0 + 3

Combine like terms: 0 + 3 = 3
1x = 3

Divide each side by '1'.
x = 3

Simplifying
x = 3

See similar equations:

| 4y^2+4y-28=0 | | 5z-4=8z-4z | | 9x+11-6x-2=2x+4+x+5 | | 2x^2-4x+22=0 | | 7c+18=-5c+78 | | 9p^2+2=11 | | 7(3s+4)=154 | | 5y-7=9+4(y-2) | | 27(x^4)+9+x=0 | | 7(3s+4)=158 | | 4(2l+2)=16 | | n*5= | | n*-5= | | 3(a-7)=15 | | x^2+7+12=(p+[1])(p+2) | | 54-n=25 | | 2n+9j=31 | | 6x+3(x+4)=8(x-3) | | U=3(8n+31)+7(n+1) | | 3(5m+2)-(4m+5)= | | B+45= | | 2x+3-7-x=2x-6-x+2 | | -4(x+3)-7=4x+13 | | n*5+8=7 | | (3z+1)=5+2 | | 2(r+h)-8=22 | | 2a+2=6-2a | | 0.03x+0.05(2500-x)=75 | | 5+22=n+16 | | 2(3x-1)=3-(-2-x) | | 3w+16=7w | | 12*x+6=-228 |

Equations solver categories